Implementation and Technical Testing of a Robot for Future Use Inpatient Care (Covid-19) - Rico Mesa, Edgar Mario; Barrientos Gómez, Juan Guillermo; Correa Zapata, Sebastian; Acevedo Urrego, Victor Alejandro; Palacios Correa, Paula Andrea; Alvarez Tobón, Verónica Andrea; Londoño Lopera, Juan Camilo; Aguilar Perez, Yudy Alexandra; Jaramillo Munera, Yomin Stiven; Torres Silva, Ever Augusto; Vergara Crismatt, Carlos Alberto; Jimenez Franco, Briam Sneider; et al. (Revista Mexicana de Ingenieria Biomedica, 2021)
The present paper describes the process of conformation in a record time of a mobile robot that has the functions of telemedicine. The robot is designed for a health institution in the city of Medellín Colombia to accompany patients and professionals in the care of the crisis caused by infection with the SARS-COV-2 virus (COVID-19). During this process, a technical test was applied to the Robot, employing medical care drills. Also, the viability of the robot in the clinic environment has been studied, presenting the positive and negative aspects through a SWOT analysis matrix and its targeting through action strategies.